Evidence for the Existence of Two Arginyl-Transfer Ribonucleic Acid Synthetase Activities in Escherichia coli - Yem, D. W. (1973)
Two arginyl-transfer ribonucleic acid (tRNA) synthetase (EC 6.1.1.13, arginine: ribonucleic acid ligase adenosine monophosphate) activities were found in extracts of Escherichia coli strains AB1132 and NP2. The two arginyl-tRNA synthetase activities in extracts of strain AB1132 were found to be separable by diethylaminoethyl-cellulose column chromatography, Sephadex column fractionation, and by sucrose density gradient centrifugation. In addition, in the standard assay using extracts of strain AB1132 there were two pH optima for arginyl-tRNA synthetase activity. Furthermore, when arginyl-tRNA synthetase of strain NP2 was fractionated by hydroxylapatite column chromatography, two activities were observed which were similar to those of strain AB1132.